Identification of a neutralizing epitope within antigenic domain 5 of glycoprotein B of human cytomegalovirus - Wiegers, Anna-Katharina; Sticht, Heinrich; Winkler, Thomas; Britt, William J.; Mach, Michael (Journal of Virology, 2015)
Human cytomegalovirus (HCMV) is an important, ubiquitous pathogen that causes severe clinical disease in immunocompromised individuals, such as organ transplant recipients and infants infected in utero. The envelope glycoprotein B (gB) of HCMV is a major antigen for the induction of virus-neutralizing antibodies. We have begun to define target structures within gB that are recognized by virus-neutralizing antibodies. Antigenic domain 5 (AD-5) of gB has been identified as an important target for neutralizing antibodies in studies using human monoclonal antibodies (MAbs). Anti-AD-5 MAbs share a target site on gB, despite originating from different, healthy, HCMV-infected donors. Mutational analysis of AD-5 identified tyrosine 280 in combination with other surface-exposed residues (the YNND epitope) as critical for antibody binding. The YNND epitope is strictly conserved among different HCMV strains. Recombinant viruses carrying YNND mutations in AD-5 were resistant to virus-neutralizing MAbs. Competition enzyme-linked immunosorbent assays (ELISAs) with human HCMV-convalescent-phase sera from unselected donors confirmed the conserved antibody response for the YNND epitope in HCMV-infected individuals and, because a significant fraction of the gB AD-5 response was directed against the YNND epitope, further argued that this epitope is a major target of anti-AD-5 antibody responses. In addition, affinity-purified polyclonal anti-AD-5 antibodies prepared from individual sera showed reactivity to AD-5 and neutralization activity toward gB mutant viruses that were similar to those of AD-5-specific MAbs. Taken together, our data indicate that the YNND epitope represents an important target for anti-gB antibody responses as well as for anti-AD-5 virus-neutralizing antibodies.HCMV is a major global health concern, and a vaccine to prevent HCMV disease is a widely recognized medical need. Glycoprotein B of HCMV is an important target for neutralizing antibodies and hence an interesting molecule for intervention strategies, e.g., vaccination. Mapping the target structures of neutralizing antibodies induced by naturally occurring HCMV infection can aid in defining the properties required for a protective capacity of vaccine antigens. The data presented here extend our knowledge of neutralizing epitopes within gB to include AD-5. Collectively, our data will contribute to optimal vaccine design and development of antibody-based therapies.
EVALuna2:8287